Lisboa en la literatura y la música vascas - Cid Abasolo, Carlos (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2009)
This article deals with the recreation of Lisbon in Basque literature and music. It is divided in three parts. The first one analyses the last Basque novel set in Lisbon: Jon Arretxe’s Fatum. In it, Lisbon is not merely a scenario, but a character in itself of the novel’s argument, a fundamental, ever-present character, with greater relevance than the main character itself, Mário Barbosa. In fact, the story is constantly interrupted with the description of streets and squares of Lisbon, in which the story develops. The second part concentrates in other works of Basque literature which refer to Lisbon and to Portugal in general, due to, in most cases, the awe that many Basque writers feel towards Fernando Pessoa. Finally, the third part deals with the connections between Lisbon and Portugal on one hand and contemporary Basque music in the other throughout its several branches (folk, rock, etc.).